Relationship Between Senior Secondary School Principals’ Administrative Skills and Teachers’ Job Performance in Adamawa State, Nigeria - Takwate, Kwaji Tizhe; Hamidu, Umaru (Innovare Journal of Education, 2025)
This study investigated the relationship between senior secondary school principals’ administrative skills and teachers’ job performance in Adamawa State, Nigeria. Four research questions and three null hypotheses guided the study using 298 school principals and 6,589 teachers as population. A sample of 124 principals and 371 teachers was drawn from three education zones using a multi-stage sampling technique. A correlation research design was adopted for the study. Principals’ administrative skills and teachers’ job performance questionnaire (PASTJPQ) were used for data collection. The reliability coefficient of the instrument was .986 using Cronbach alpha. Mean scores, standard deviations, and Pearson Product Moment Correlation Coefficient were used to answer the research questions and hypotheses, respectively. The study found the relationship between senior secondary school principals’ administrative skills and teachers’ job performance significant (on the level of personnel administrative skill, financial, administrative skills, and principals’ pedagogical skills efficiency) in Adamawa State. The study concluded that senior secondary school principal’s administrative skills were significantly related to teachers’ job performance in Adamawa State. Based on these findings, the study recommended, among others, that principals should employ more robust supervisory strategies and skills in their supervision of the teaching and learning process to improve the performance of teachers and also set up a functional school base management committee (SBMC)to foster the community-school efforts in the interest of enhancing school effectiveness and improving teachers’ job performance.